Hubungan pemanfaatan koleksi bahan pustaka dengan memenuhi kebutuhan informasi pengguna - Thalia Rizky Augustine; Prijana Prijana; Saleha Rodiah (Faculty of Communication, Padjadjaran University, 2021)
The use of library material collections is essential in meeting the user’s information needs in Community Reading Park (TBM). The development of science and technology affects people's need for information because of their curiosity and desire to improve knowledge. In fulfilling information needs, Community Reading Park is one of places providing information sources that can be used by the community. This study aims to determine the relationship between the utilization of library material collections and fulfilling the users’ information needs in Community Reading Park of Batoe Api. The use of library material collections was measured with some criteria: frequency, duration, reasons, objectives, facilities, coziness, and completeness. Fulfilling information needs was measured with the dimensions of current need approach, everyday need approach, exhaustic need approach, and catching-up need approach. This study was quantitative with correlation method. Data collection techniques in this article were questionnaire, observation, and library research. The sampling method used in this study was taken from one of the probability sampling methods, namely simple random sampling. The population in this study were 150 members of Community Reading Park of Batoe Api. The analysis technique used was descriptive method of data analysis and inferential analysis. The results of this study indicate a significant relationship between the utilization of library material collections and fulfilling information needs with dimensions of the four approaches mentioned above. In terms of book arrangement, TBM Batoe Api did well, and in the future, it is hoped that the arrangement can follow that of the library national standards despite its status as a Community Reading Park.